Indonesia's City Diplomacy in Promoting Global Sustainability Context through Urban Networks - Ahmad Harakan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The present research investigates the function of urban diplomacy in promoting sustainable initiatives in the swiftly urbanising setting of Indonesia. The study concentrates on the way urban networks facilitate the dissemination of knowledge, resources, and optimal practises among local administrations. Through the examination of diverse urban networks, including inter-city partnerships, cross-border municipal networks, and regional programmes, this study underscores their role in bolstering local capabilities and advancing sustainable urban development strategies in domains such as waste disposal, ecological infrastructure, and climate change resilience. Furthermore, the research investigates the supportive function of the national government of Indonesia in urban networks and city diplomacy endeavours, showcasing its dedication to urban sustainability via policies and international collaborative endeavours. The study highlights the capacity of urban networks and city diplomacy to promote global sustainability in Indonesia. It proposes that cultivating strong urban networks and efficient city diplomacy can substantially aid in achieving a sustainable future for both the country and the regional.